Efikasi Diri dalam Melakukan Diet Sehat pada Masyarakat Desa Cipacing, Sumedang - Nisa, Hilmi Khairun; Juniarti, Neti; Mulya, Adelse Prima (UI Scholars Hub, 2025)
Background. Noncommunicable diseases (NCDs) account for 57 million deaths (71%) worldwide and 73% of all deaths in Indonesia. Eating habits are one of the factors contributing to the incidence of NCDs. In the process of improving a healthy lifestyle, including a healthy diet, self-confidence or self-efficacy in maintaining a healthy diet is necessary. Objective. This study aims to identify the level of self-efficacy in maintaining a healthy diet among the community in Cipacing Village, Sumedang. Methods. This study was conducted using a quantitative descriptive research design among the community of Cipacing Village, Sumedang Regency, West Java. The sample was taken using non-probability sampling, namely accidental sampling, so that the total sample taken was 100 respondents. Data collection was carried out using the Self-Efficacy to Regulate Eating Habits Questionnaire, which has been tested for validity and reliability with a Cronbach's alpha value 0.912. Data were analyzed using univariate analysis frequencies distribution. Results. The results showed that the majority of respondents had low to moderate self-efficacy levels, namely 69%, thus requiring a special intervention and approach to increase self-efficacy in implementing a healthy diet in the community and prevent the risk of NCDs.